Intraoperative Non-Opiate Anesthesia for Patients Undergoing Arthroscopic Temporomandibular Joint Surgery: A Randomized Controlled Trial - Ma H; Perez J; Bertsch J; Albanese ML; Korn EG; Mueller A; Houle T; Burris BJ; McCain J; Wang J (Drug Design, Development and Therapy)
He Ma,1,2 Juan Perez,2 Julia Bertsch,2 Marissa L Albanese,2 Elizabeth G Korn,2 Ariel Mueller,2 Timothy Houle,2 Briana June Burris,3 Joseph McCain,3 Jingping Wang2 1Department of Anesthesiology, the Second Hospital of Jilin University, Changchun, People’s Republic of China; 2Department of Anesthesia, Critical Care and Pain Medicine, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 3Department of Oral & Maxillofacial Surgery, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Jingping Wang, Department of Anesthesia, Critical Care and Pain Medicine, Massachusetts General Hospital, Harvard Medical School, 55 Fruit Street, GRJ 420, Boston, MA, 02214, USA, Tel +1 (617) 643 2729, Email jwang23@MGH.Harvard.eduBackground: Pain intensity after temporomandibular joint (TMJ) surgery is often underestimated, and inadequate pain control may relate to poor recovery quality, increased opioid consumption, and longer hospital stay. This trial aims to evaluate whether non-opiate anesthesia provides a promising option of pain management for patients undergoing TMJ surgery.Methods: Sixty patients receiving TMJ surgery were randomly assigned to either the control group or the non-opiate group. Non-opiate anesthesia used lidocaine, dexmedetomidine, and ketamine infusion therapy for pain management. The primary outcome was the highest documented pain score while in the post-anesthesia care unit (PACU). Secondary outcomes included perioperative opioid consumption, utilization, dosage, and timing of rescue analgesia in the PACU, incidence of postoperative nausea and vomiting in the PACU and at home, pain satisfaction levels, occurrence of opioid-related adverse effects, duration of PACU and hospital stays, and total consumption of oxycodone-acetaminophen tablets at 24 and 48 hours post-surgery.Results: Patients were predominantly female (88.3%) and had a median age of 37.5 [IQR 26.0, 52.5] years. There were no significant differences observed in the highest documented pain scores (mean difference [MD] − 0.36 points, 95% CI: − 1.84, 1.12, p = 0.63), postoperative oxycodone-acetaminophen consumption (MD 6.68 mg, 95% CI: − 2.48, 15.84, p = 0.15), pain satisfaction (odds ratio [OR] 0.81, 95% CI: 0.23, 2.81, p = 0.74), time to PACU discharge (hazard ratio [HR] 1.24, 95% CI: 0.67, 2.30, p = 0.49) or time to hospital discharge (HR 1.48, 95% CI: 0.80, 2.75, p = 0.21) between the two groups. Similarly, no significant difference was observed in time to rescue analgesia, calculated in minutes from the end of surgery (HR 1.69, 95% CI: 0.79, 3.61, p = 0.18).Conclusion: Non-opiate anesthesia for pain management shows a similar postoperative analgesia effect, compared to opioid-based anesthesia, in patients undergoing arthroscopic TMJ surgery.Keywords: non-opiate, anesthesia, temporomandibular joint disorders, temporomandibular joint, surgery